Survey Minat Studi Lanjut Ke Perguruan Tinggi Siswa Siswi Calon Lulusan SMA Dan SMK Di Kota Dan Kabupaten Bogor Pada Program Studi Administrasi Bisnis - Amwila, Andi Yudha (Jurnal Ilmiah Manajemen Kesatuan, 2016)
High school students should already be thinking about the plan to continue their study to higher levels in accordance with their interests. Many programs offered by public and private universities, one of them is Business Administration Program. The aims of this research are, firstly to examine the significance of interests of high school students in the city and region of Bogor, specifically on choosing the Business Administration program. Secondly, this research tries to investigate the factors influencing the interests of high school students to continue their study in higher education. The method used in this research is descriptive statistics using Survey. Data collection is conducted by way of observations assisted with questionnaire instruments and interview. Samples are gathered using Purposive Sampling. Slovin formula is used to determine the amount of samples needed. The results show that the students are interested in taking the major of Business Administration and that they are supported with Office Administration background in their current study, this is followed by other students with different backgrounds. The research concludes that high school students’ interest in Business Administration Program is influenced by their own current background study. Other factors also significant in influencing the students’ interest are the parents’ social condition and the campus’ facilities.